Bone Marrow-Derived Multipotent Stromal Cells Promote Myocardial Fibrosis and Reverse Remodeling of the Left Ventricle - Timur Fatkhudinov; Galina Bolshakova; Irina Arutyunyan; Andrey Elchaninov; Andrey Makarov; Evgeniya Kananykhina; Oksana Khokhlova; Arkady Murashev; Valeria Glinkina; Dmitry Goldshtein; Gennady Sukhikh (Hindawi Limited, 2015)
Cell therapy is increasingly recognized as a beneficial practice in various cardiac conditions, but its fundamentals remain largely unclear. The fates of transplanted multipotent stromal cells in postinfarction cardiac microenvironments are particularly understudied. To address this issue, labeled multipotent stromal cells were infused into rat myocardium at day 30 after myocardial infarction, against the background of postinfarction cardiosclerosis. Therapeutic effects of the transplantation were assessed by an exercise tolerance test. Histological examination at 14 or 30 days after the transplantation was conducted by means of immunostaining and quantitative image analysis. An improvement in the functional status of the cardiovascular system was observed after both the autologous and the allogeneic transplantations. Location of the label-positive cells within the heart was restricted to the affected part of myocardium. The transplanted cells could give rise to fibroblasts or myofibroblasts but not to cardiac myocytes or blood vessel cells. Both types of transplantation positively influenced scarring processes, and no expansion of fibrosis to border myocardium was observed. Left ventricular wall thickening associated with reduced dilatation index was promoted by transplantation of the autologous cells. According to the results, multipotent stromal cell transplantation prevents adverse remodeling and stimulates left ventricular reverse remodeling.